2020
DOI: 10.3390/ijms21041420
|View full text |Cite
|
Sign up to set email alerts
|

β3-Adrenoreceptor Blockade Induces Stem Cells Differentiation in Melanoma Microenvironment

Abstract: Although there is an increasing evidence that cancer stem cell (CSC) niches in the tumor microenvironment (TME) plays a crucial role in sustaining solid tumors progression, several molecular players involved in this regulation still remain unknown. The role of β-adrenergic signaling in enhancing tumor growth through β2-adrenoreceptors (β2-ARs) has been confirmed in different cancer models, but the role played by the β3-adrenergic receptor (β3-AR) has recently emerged. Previous studies showed that β3-AR promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In this respect, it has recently been demonstrated that β3-AR is widely expressed in the most frequent neoplasms occurring in pregnant women [22] and its blockade reduces cancer progression [14][15][16][17][18]. In particular, SR59230A, administered intratumorally at 5 mg/kg, has been shown to decrease melanoma growth by inducing neoplastic cell death and inhibiting tumor vascularization [15] while, when administered intraperitoneally at 10 mg/kg and 20 mg/kg, it reduced neuroblastoma [18] and melanoma [35] progression, respectively. These latter studies, indicating that SR59230A exerted marked anticancer effects upon intraperitoneal administration at the noted dosage [35], were the background to the present experiments in which we investigated the effects on the DA of SR59230A, administered intraperitoneally at 10, 20 and 40 mg/kg, both in acute and chronic mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it has recently been demonstrated that β3-AR is widely expressed in the most frequent neoplasms occurring in pregnant women [22] and its blockade reduces cancer progression [14][15][16][17][18]. In particular, SR59230A, administered intratumorally at 5 mg/kg, has been shown to decrease melanoma growth by inducing neoplastic cell death and inhibiting tumor vascularization [15] while, when administered intraperitoneally at 10 mg/kg and 20 mg/kg, it reduced neuroblastoma [18] and melanoma [35] progression, respectively. These latter studies, indicating that SR59230A exerted marked anticancer effects upon intraperitoneal administration at the noted dosage [35], were the background to the present experiments in which we investigated the effects on the DA of SR59230A, administered intraperitoneally at 10, 20 and 40 mg/kg, both in acute and chronic mode.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SR59230A, administered intratumorally at 5 mg/kg, has been shown to decrease melanoma growth by inducing neoplastic cell death and inhibiting tumor vascularization [15] while, when administered intraperitoneally at 10 mg/kg and 20 mg/kg, it reduced neuroblastoma [18] and melanoma [35] progression, respectively. These latter studies, indicating that SR59230A exerted marked anticancer effects upon intraperitoneal administration at the noted dosage [35], were the background to the present experiments in which we investigated the effects on the DA of SR59230A, administered intraperitoneally at 10, 20 and 40 mg/kg, both in acute and chronic mode. Of note, this study was carried out on healthy dams, without evaluating the anticancer properties of SR59230A.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we aimed to suggest that the β3-AR agonist could be tested in the first phase of transplantation to maintain low to moderate levels of ROS, and to preserve stemness and long-term differentiation. When HSCs start to differentiate, ROS must be kept at moderate/high levels to stimulate hematopoietic differentiation, as previously demonstrated in melanoma [ 96 , 99 ]. However, as the molecular biomarkers have not yet been identified, it is hard to state the necessary dose and timing of agonists/antagonists’ administration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Adrβ3 inhibition in myeloid cells switches macrophage and neutrophil phenotypes to immunocompetent M1 and N1 types, respectively, indicating additional mechanisms of Adrβ3 blockers in checking tumors (29). Adrβ3 signals also enrich stromal population by recruiting and maintaining hemopoietic (HSC) and mesenchymal stem cells (MSC) favoring tumor aggression, while Adrβ3 blockade was shown to promote local differentiation of HSC to lymphoid/myeloid lineages and MSC to adipocyte lineages in melanoma favoring a less aggressive tumor milieu (30).…”
Section: Adrenergic Signals As Tumor Promoters: Molecular Mechanismsmentioning
confidence: 99%